Pengaruh Partisipasi Penyusunan Anggaran dan Kegunaan Sistem Informasi Akuntansi Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variabel Moderasi (Studi Empiris Pada RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah) - Meirina Septiningrum; Endah Winarti; Subchan Subchan (MAKSIMUM, 2019)
Employee performance is a matter that is very much considered by a company so that the company can be more advanced due to good employee performance. The purpose of this study is to empirically examine the effect of budgetary participation and the usefulness of accounting information systems on employee performance with organizational commitment as a moderating variable. The study population was all employees of Dr. Amino Gondohutomo, Central Java Province. Total employee samples amounted to 180 respondents taken using a questionnaire distributed directly to employees, but which can be processed by 163 respondents. The data used is primary data using the questionnaire data collection method. The method of analysis in this study is Moderated Regression Analysis (MRA).From this research, it can be concluded that budgetary participation and the usefulness of accounting information systems have a significant positive effect on employee performance. The higher budgeting participation and the usefulness of accounting information systems, the higher the performance of employees. This study also found that organizational commitment can moderate the relationship between budgeting participation and the usefulness of accounting information systems to employee performance with a significant positive direction. The higher budgeting participation and the usefulness of accounting information systems, with high organizational commitment will improve employees performance.